Health Education Isi Piringku Terhadap Perilaku Ibu dalam Pemenuhan Nutrisi Pada Anak Pra Sekolah (3-5 Tahun) Di RA Al-Fajar Kandat Kecamatan Kandat - Nurhasanah, Nurhasanah; Wahyuni, Candra (Judika (Jurnal Nusantara Medika), 2020)
Difficulty eating in children often occurs in pre-school children by> 20%. Factors that emphasize how to feed children, eating atmosphere and food variations and factors given to children, meal times and frequency of eating children. Problems with eating difficulties in children can be bad for children's growth and development. Children can enjoy undernourished food (Underweight) because the food needed is in small amounts so it does not meet their nutritional needs. The purpose of this study is to analyze Health Education "contents of my plate" of mothers about the fulfillment of nutrition in pre-school children (3-5 years) in RA AL-FAJAR Kandat District Kandat in 2020. This study uses a simple random sampling technique with one groip pretest-post method in 40 mothers in RA AL-FAJAR Kandat Kandat District. The parameters used are the questionnaire answers to the contents of my plate. The results of the data collection were processed by Wilcoxon statistical test. The results of the analysis obtained (0,000) <α (0.05) means that there are differences in the results before and after health education of the contents of my plate for mothers in fulfilling nutrition in pre-school children (3-5 years) in RA AL-FAJAR Kandat Kandat District. The conclusion is that the provision of information about nutrition fulfillment for infants will increase the mother's knowledge and fulfillment process, because the mother's knowledge plays an important role in determining the fulfillment of nutrition in fulfilling nutrition.